Pengaruh Kualitas Pelayanan, Harga Dan Promosi Terhadap Loyalitas Pelanggan Pt Batam Trans - Harianja, Josepin; Dominika Dewa, Dominika Dewa; Nuraeni, Brigida Endah (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2022)
This study aims to determine the effect of service quality, price and promotion on customer loyalty at PT Batam Trans. The sample of this research is the customers of PT Batam Trans, totaling 111 people. Data collection techniques in this research are literature study, observation, and questionnaires, while the data analysis techniques used are classical assumption test, multiple linear regression, T test, F test, and coefficient of determination. The results showed that there was no positive and significant effect between the variables of service quality and customer loyalty, as evidenced by tcount 0.321<ttable 1.980 with a significance level of 0.113>0.05, there was no positive and significant effect between the price and customer loyalty variables. with tcount 0.404 < ttable 1.980 with a significance level of 0.035<0.05. There is a positive and significant effect between promotions and customer loyalty, as evidenced by tcount t11.054>ttable 1.980 with a significance level of 0.032<0.05. There is a significant effect between service quality, price, promotion on customer loyalty, as evidenced by Fcount 138,609>2.99 with a significance of 0.000<0.05. Furthermore, the value of Adjusted R Square obtained is 0.795, indicating about 79.50% of the influence of service quality, price and promotion on customer loyalty